2015
DOI: 10.1161/strokeaha.114.006864
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Pituitary Adenylate Cyclase–Activating Polypeptide Delivery After Brain Stroke Improves Functional Recovery by Inducing M2 Microglia/Macrophage Polarization

Abstract: 520S troke is a leading cause of death and long-term disabilities worldwide. Despite years of intense research and preclinical identification of numerous potential neuroprotective compounds, the only available treatment for brain ischemia relies on thrombolysis through injection of a recombinant tissuetype plasminogen activator. However, the treatment benefits to <10% of stroke victims because of a narrow therapeutical time window (<4.5 hours after stroke onset) and side effects. Consequently, there is a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…Treatment with VIP prevented several features of mechanically induced brain trauma, such as microglial activation, proinflammatory cytokine secretion, leukocyte infiltration, and neurodegeneration [133]. In a model of brain focal ischemia, delayed intracerebroventricular delivery of PACAP-producing stem cells promoted fast and stable functional recovery which correlated with reduced inflammatory response and increased number of AG1 + microglia, further supporting a role for PACAP in polarizing microglia towards an M2 neuroprotective phenotype [134]. In an in vitro model of ischemic damage by oxygen and glucose deprivation (OGD) and reoxygenation, pretreatment of BV-2 cells with PACAP alleviated hypoxic injury by preventing TLR4/MyD88/NF- κ B signaling and decreasing proinflammatory cytokine levels and BV-2 apoptosis [135].…”
Section: Vip and Pacapmentioning
confidence: 99%
“…Treatment with VIP prevented several features of mechanically induced brain trauma, such as microglial activation, proinflammatory cytokine secretion, leukocyte infiltration, and neurodegeneration [133]. In a model of brain focal ischemia, delayed intracerebroventricular delivery of PACAP-producing stem cells promoted fast and stable functional recovery which correlated with reduced inflammatory response and increased number of AG1 + microglia, further supporting a role for PACAP in polarizing microglia towards an M2 neuroprotective phenotype [134]. In an in vitro model of ischemic damage by oxygen and glucose deprivation (OGD) and reoxygenation, pretreatment of BV-2 cells with PACAP alleviated hypoxic injury by preventing TLR4/MyD88/NF- κ B signaling and decreasing proinflammatory cytokine levels and BV-2 apoptosis [135].…”
Section: Vip and Pacapmentioning
confidence: 99%
“…It was shown that the switch from M1 to M2 is delayed with ageing (Gordon, 2003; Lee et al, 2013; Miron and Franklin, 2014). Various studies demonstrated the beneficial role of M2 cells in protection against stoke and in the recovery stage (Brifault et al, 2015; Li et al, 2016; Liu et al, 2016). It was reported that M2 microglia/macrophages infiltrated the ischemic core at 24 hrs, peaking at 5 days, and declining in the striatum by 14 days.…”
Section: Treating Stroke In Middle-aged and Old Mice With Partial Mhcmentioning
confidence: 99%
“…M2 microglia protect neighboring cells by removing cell debris and releasing trophic factors for brain repair, based on their ability to produce interleukin 4 (IL-4) and IL-10 [6]. Meanwhile chronically-activated M1 microglia exacerbate brain injury by producing neurotoxic substances, although they participate in clearing cell debris in the early stages after stroke [7]. Microglia/macrophage phenotype polarization is likely dependent on activation status, and balancing this polarization is a promising therapeutic strategy for stroke treatment.…”
Section: Introductionmentioning
confidence: 99%